Sub-Saharan red cell antigen phenotypes and glucose-6-phosphate dehydrogenase deficiency variants in French Guiana. (December 2016) - Petit, Florence; Bailly, Pascal; Chiaroni, Jacques; Mazières, Stéphane
Abstract Background The treatment ofPlasmodium vivax infections requires the use of primaquine, which can lead to severe haemolysis in glucose-6-phosphate dehydrogenase (G6PD)-deficient individuals. However, most of the Latin American countries, which are still endemic forvivax malaria, lack information on the distribution of G6PD deficiency (G6PDd). No survey has been performed so far in French Guiana. Herein, 80 individuals of the French Guianan Noir Marron population were scrutinized for red cell surface antigens of six blood group systems (ABO, Rh, Kell, Kidd, Duffy and MNS) and G6PD genetic polymorphisms. First, the sub-Saharan origin of the red cell phenotypes was assessed in relation with the literature. Then, given that the main sub-Saharan G6PDd variants are expected to be encountered, only theG6PD sequences of exons 4, 5, 6 and 9 were screened. This work aims at appraising theG6PD gene variation in this population, and thus, contributing to the G6PD piecemeal information in Latin America. Results Ninety-seven percent (97 %) of the red cells are Fy(a− b−), either D+ C− E− c+ e+ or D+ C+ E− c+ e+ and 44 % exhibited the Fya−/Jkb−/S− combined phenotype. Noteworthy is the detection of the G6PD(Val68Met) variant characterized by c.202G > A transition, G6PD(Asn126Asp) variant characterized by c.376A>G transition and G6PD(Asp181Val) variant characterized by c.542A>T transversion of theG6PD gene in 22.5 % of the sample, characteristic of the A−(202), A and Santamaria G6PDd variants, respectively. Conclusions French Guianan Noir Marron population represents a pool of Rh-D antigen positive, Duffy-negative and G6PD-deficient erythrocytes, the latter accounting for one in every eight persons. The present study provides the first community-based estimation of the frequency of G6PDd polymorphisms in French Guiana. These results contribute to the G6PD genetic background information puzzle in Latin America.